INTEGRATING UZBEK FOLK TALES INTO ENGLISH LANGUAGE LESSONS FOR 7TH GRADE STUDENTS USING MODERN METHODS (Web of Teachers: Inderscience Research, 2025)
This article analyzes innovative methods for integrating Uzbek folk tales into 7th-grade English language lessons. It also examines the linguistic and cultural features of colloquial phraseologisms in Uzbek and English. These studies aim to assist teachers in enhancing student engagement and developing their language skills during lessons.